Pharmacotherapy of Psychotic Disorders in Türkiye: Insights From a National Prescription Database - Sena Türkeş; Aybeniz Civan Kahve; Taner Çin; Esra Şafak Yılmaz; Hakkı Gürsöz; Süreyya Barun (Brain and Behavior)
ABSTRACT Objective Psychotic disorders, affecting 3–7 per 1000 individuals, significantly impair mental functioning. Although antipsychotic medications represent the mainstay of treatment, prescribing practices can vary based on patient characteristics and across different countries. Currently, national epidemiological data on psychotropic prescribing patterns in Türkiye are lacking, and understanding these variations is crucial for informing treatment guidelines and optimizing patient care. Methods Data from the Turkish Prescription Information System (PIS) for the year 2019 were analyzed to evaluate antipsychotic prescribing patterns for psychotic disorders. Included were prescriptions for schizophrenia, other specified psychotic disorders not attributable to a substance or known physiological condition, and unspecified psychosis with the same exclusion criteria. Results Second‐generation antipsychotics (SGAs) constituted 80% of all prescriptions, making them the most frequently prescribed class in Türkiye. This finding is consistent with other national studies. Quetiapine was the most frequently prescribed SGA overall, although prescribing patterns varied by age group. Although SGAs were the most commonly prescribed class, typical antipsychotics or first‐generation antipsychotics (FGAs) remained in use, particularly haloperidol in patients aged ≥80 years. Conclusions This national study demonstrates the widespread use of SGAs in Türkiye, particularly quetiapine, while also highlighting the continued use of FGAs, especially haloperidol, in older adults. These findings highlight the need for further research on age‐specific prescribing practices and the development of tailored treatment guidelines. Furthermore, international comparisons of prescribing patterns should be conducted to identify potential variations and explore their underlying causes.